2018
DOI: 10.18203/2349-3291.ijcp20181551
|View full text |Cite
|
Sign up to set email alerts
|

Study of prevalence, etiology, response to treatment and outcome of paediatric shock in a tertiary care hospital

Abstract: Background: Shock accounts for 2% of children admitted to Paediatric casualty worldwide as per most western literature and in Nelson text book of Paediatrics. About 10 million children die of shock every year in the world. Highest mortality is observed in under 5 children in developing countries. Clinical manifestations are due to decreased perfusion to tissues, the compensatory mechanisms that are triggered by the decreased perfusion and the inadequate removal of metabolic wastes. This study was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 6 publications
3
2
6
Order By: Relevance
“…Our observation related to Septic shock prevalence which is 32.2% of the total shock patients is in contrast with the reports from India which showed septic shock was the commonest [10,11]. Again, this could be due to the difference between the settings of the studies.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Our observation related to Septic shock prevalence which is 32.2% of the total shock patients is in contrast with the reports from India which showed septic shock was the commonest [10,11]. Again, this could be due to the difference between the settings of the studies.…”
Section: Discussioncontrasting
confidence: 97%
“…Comparable outcome was also reported by Vasundhara et.al, 2017 [10]. Mortality rate in our study among septic shock patients is 50% similar high mortality rate was also reported by other studies [5,10,11,14].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…5 All children with shock must be administered high flow oxygen as there is tissue hypoxia. 6 Rapid boluses of RL or NS at 20 mi/kg in 5-10 mm are given. 7 In patients with fluid refractory shock, pharmacological support using vasoactive amines is a choice of treatment.…”
Section: Introductionmentioning
confidence: 99%